Model Pengelolaan Perkebunan Kelapa Sawit Berkelanjutan Pada Lahan Gambut di Provinsi Riau - Nasrul, Besri; Hamzah, Anthony; Nedi, Syahril (Jurnal Agro Teknologi Tropika, 2012)
A model of sustainable oil palm management in the tropical peatlands in Riau, precise and comprehensive data ofland and social economic farmers are required. The research has conducted in the Riau District four months by usingfield survey on land unit. The lands were had evaluated by maximum limiting factors and the socio-economic werecalculated by Multi-Dimensional Scaling. Oil palm development exist in the peatland affected on: 1) DHL score whichexceeds saturation level of 4 mS, and the highest score in Bengkalis 107,32 mS; 2) Land subsidence > 6 cm year-1especially Rokan Hilir have 18 cm year-1; 3) Change of ground water exceeding value float for oil palm (60 cm), highestvalue there was Siak 30-95 cm; 4) Level continue oil palm plantation in peatlands for the ecology dimension showedindex 47,35% (less have continuation) with ecology factor having an effect: water level, prevention of burning land,usage of amelioran /fertilization, and specific of site technology; 5) For social dimension showed index 55,65% (enoughhave continuation) with social factor having an effect: community empowerment, policy synchronization, solving of sosio-conflict, and weak of law straightening; 6) For economic dimension showed index 68,62% (enough have continuation)with economic factor having an effect: capital structure, price of fruit, and production equipments.